2019
DOI: 10.1183/13993003.01512-2018
|View full text |Cite
|
Sign up to set email alerts
|

Pneumoniaversusgraft dysfunction as the cause of acute respiratory failure after lung transplant: a 4-year multicentre prospective study in 153 adults requiring intensive care admission

Abstract: We aimed to assess the main causes of intensive care unit (ICU) readmissions in lung transplant adults and to identify independent predictors of ICU mortality (primary end-point).This Spanish five-centre prospective cohort study enrolled all lung transplant adults with ICU readmissions after post-transplant ICU discharge between 2012 and 2016. Patients were followed until hospital discharge or death.153 lung transplant recipients presented 174 ICU readmissions at a median (interquartile range) of 6 (2–25) mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Moreover, for LTRs, it has been described that pneumonia is a main and independent predictor of mortality upon ICU admission. 27 Our study has some limitations that need to be addressed. First, data regarding the outcome of some patients are lacking because they were still hospitalized at the time of last follow-up.…”
Section: Ta B L E 3 Treatment and Outcomesmentioning
confidence: 94%
“…Moreover, for LTRs, it has been described that pneumonia is a main and independent predictor of mortality upon ICU admission. 27 Our study has some limitations that need to be addressed. First, data regarding the outcome of some patients are lacking because they were still hospitalized at the time of last follow-up.…”
Section: Ta B L E 3 Treatment and Outcomesmentioning
confidence: 94%
“…In these cases, bronchoscopy to rule out infection is usually performed before commencing empirical medical therapy for infection or rejection. 81,82 Transbronchial biopsies can also be considered to confirm the diagnosis of rejection or infection; however, caution should be used in ventilated patients for the high risk of bleeding (greater than 20%) and pneumothorax (6 to 10%). 83 Although the immunosuppressive drug regimens have not changed significantly over recent years, the understanding of how to optimize immunosuppression has improved.…”
Section: Current Trends and Future Insights On Immunosuppressive Ther...mentioning
confidence: 99%
“…4 Study variables were reported elsewhere. 4 PCT plasma levels samples were obtained within 24 hours after ICU-A. Patients were followed until hospital discharge or death.…”
Section: Methodsmentioning
confidence: 99%
“…All clinical data were collected prospectively by the investigators, as part of a multicenter study reported elsewhere 4 . Study variables were reported elsewhere 4 . PCT plasma levels samples were obtained within 24 hours after ICU‐A.…”
Section: Methodsmentioning
confidence: 99%